Electrolyte, battery and electric device

By using dual-silicon-based system additives in lithium-ion batteries to build a stable interface mask, the problem of degradation in high and low temperature environments is solved, the circulation and storage performance of the battery is significantly improved, and the service life of the battery is extended.

CN119674232AInactive Publication Date: 2025-03-21GUANGZHOU TINCI MATERIALS TECH

Patent Information

Application Number
CN202411739271.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The performance of lithium-ion batteries in high-temperature and low-temperature environments has decreased. The existing electrolyte additives have limited performance improvement under high voltage conditions, and solvent decomposition causes H+ and F- to corrode the positive electrode material, consume active ions, and reduce battery capacity.

Method used

The bisilicon-based system additives including difluorophosphate and silicone borate are used to improve the oxidation resistance of the electrolyte, and a dense and stable solid electrolyte interface film is built to inhibit gas production and improve the battery's normal temperature circulation, high temperature circulation, high temperature storage and low temperature discharge performance.

Benefits of technology

It significantly improves the battery's room temperature circulation, high-temperature circulation, high-temperature storage and low-temperature discharge performance, reduces the interface impedance, accelerates the transmission of active ions, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674232A_ABST
    Figure CN119674232A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of batteries, and particularly discloses an electrolyte, a battery and an electric device, the electrolyte comprises a solvent, an electrolyte salt and a first additive, the first additive comprises silicon difluorophosphate as shown in a formula 1 and silicon borate as shown in a formula 2: # imgabs0. The electrolyte is used in the battery, so that the normal-temperature cycle, high-temperature cycle, high-temperature storage and low-temperature discharge performance of the battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of battery technology, and specifically relates to an electrolyte, a battery and an electrical device. Background Art

[0002] With the advancement of science and technology and the diversification of energy demand, traditional energy is being consumed at an accelerated pace, and countries are constantly accelerating their strategic deployment of new energy technologies. Among them, power batteries are rising rapidly with the development of new energy vehicles, and energy storage batteries are also booming with the development of clean energy. In recent years, the competition in the new energy vehicle industry has become increasingly fierce. Various power battery companies have continuously developed and updated their products in order to find a chemical power system that can better adapt to the market, so as to meet users' requirements for high specific energy and endurance, in order to be able to replace traditional energy passenger cars and buses in all aspects. Lithium-ion batteries have attracted widespread attention due to their many advantages, but problems such as performance degradation when working in high and low temperature environments have always plagued the development of lithium-ion batteries. The effective use of electrolyte additives is one of the methods to improve the overall performance of batteries, but the existing additives still have limited effect on improving the performance of batteries under high voltage conditions, and the electrolyte solvents will inevitably decompose, and the H produced after decomposition will + 、F - The positive electrode active material will be corroded, and the products of solvent decomposition will also consume active ions and reduce battery capacity. Therefore, the technology related to electrolyte additives needs to be further improved. Summary of the invention

[0003] The present application aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the present application proposes an electrolyte, a battery and an electrical device having excellent normal temperature cycle, high temperature cycle, high temperature storage or low temperature discharge performance.

[0004] In a first aspect, the present application provides an electrolyte solution, comprising a solvent, an electrolyte salt and a first additive, wherein the first additive comprises a difluorosilyl phosphate ester represented by Formula 1 and a boric acid silyl ester represented by Formula 2;

[0005]

[0006] wherein R1, R2 and R3 are each independently selected from any one of H, F, C1-C4 alkyl, C1-C4 fluoroalkyl, C2-C4 alkenyl, C2-C4 fluoroalkenyl, C2-C4 alkynyl, C2-C4 fluoroalkynyl, C5-C7 cycloalkyl, phenyl, R'-substituted phenyl and R"-substituted benzyl;

[0007] R ’, R" are each independently selected from any one of halogen, C1-C4 alkyl, C2-C4 alkenyl, C2-C4 alkynyl, C1-C4 fluoroalkyl, C2-C4 fluoroalkenyl, C2-C4 fluoroalkynyl;

[0008] R4 to R 12 Each is independently selected from any one of C1-C10 alkyl, C1-C10 haloalkyl, C2-C10 alkenyl, C2-C10 haloalkenyl, C2-C10 alkynyl, C2-C10 haloalkynyl, halogen and cyano.

[0009] The additives used in this application improve the oxidation resistance of the electrolyte. When applied to batteries, a denser and more stable solid electrolyte interface membrane (interface membrane for short) can be constructed with fewer side reactions, which can effectively inhibit gas production, thereby significantly improving the room temperature cycle performance, high temperature cycle performance, high temperature storage performance, and low temperature discharge performance of the battery. At the same time, it can accelerate the transmission of active ions, reduce interface impedance, and improve the battery's kinetic performance.

[0010] In some embodiments, the difluorosilyl phosphate represented by Formula 1 includes at least one of the following compounds:

[0011]

[0012] This is beneficial to improving the thermal stability and ion conductivity of the interface film, reducing the amount of positive electrode transition metal dissolved in the electrolyte, inhibiting the catalysis of transition metal ions on the electrolyte, and preventing the reduction and deposition of transition metal ions on the negative electrode surface.

[0013] In some embodiments, R4 to R 12 Each is independently selected from any one of C1-C4 alkyl, C2-C4 alkenyl, C2-C4 alkynyl, halogen and cyano.

[0014] In some embodiments, the boric acid silyl ester represented by Formula 2 comprises at least one of the following compounds:

[0015]

[0016] This helps to reduce the damage of HF and transition metal ions to electrode materials and the decomposition of electrolytes, lower interface impedance, and accelerate lithium ion transmission.

[0017] In some embodiments, based on the total mass of the electrolyte, the amount of the difluorosilicone phosphate shown in Formula 1 is 0.05% to 5%; in some specific examples, the amount of the difluorosilicone phosphate shown in Formula 1 is 0.5% to 2.5%. This is conducive to building a stable interface film, improving the flexibility and smoothness of the interface film, and improving the thermal stability and lithium ion conductivity of the interface film.

[0018] In some embodiments, based on the total mass of the electrolyte, the amount of the boric acid ester shown in Formula 2 is 0.1% to 1%; in some specific examples, the amount of the boric acid ester shown in Formula 2 is 0.3% to 0.7%. This helps to reduce the damage of HF and transition metal ions to the electrode material and the decomposition of the electrolyte, reduce the impedance of the interface film, and make it easier for lithium ions to be inserted and removed.

[0019] In some embodiments, the electrolyte salt includes at least one of lithium hexafluorophosphate, lithium difluorophosphate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium perchlorate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(oxalatoborate) and lithium difluorooxalatoborate. Thus, the material source is wide, which is conducive to improving the conductivity and electrochemical stability of the electrolyte.

[0020] In some embodiments, the solvent includes at least one of propylene carbonate, ethyl methyl carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, fluoroethylene carbonate, γ-butyrolactone, cyclopentane, methyl formate, ethyl formate, propyl formate, butyl formate, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, propyl propionate, butyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate, and butyl butyrate. Thus, the material source is wide, which is conducive to dissolving the electrolyte salt.

[0021] In some embodiments, based on the total mass of the electrolyte, the mass content of the electrolyte salt is 12% to 17%; in some specific examples, the mass content of the electrolyte salt is 12% to 15%. Within the above mass content range, the electrolyte has better conductivity and electrochemical stability.

[0022] In some embodiments, based on the total mass of the electrolyte, the mass percentage of the solvent is 10% to 90%. Within the above mass percentage range, the solvent can better dissolve the electrolyte salt and improve the electrochemical stability.

[0023] The second aspect of the present application provides a battery, comprising the electrolyte described in the first aspect. The battery has good room temperature cycle performance, high temperature cycle performance, high temperature storage performance and low temperature discharge performance, and has low gas production and a long service life.

[0024] The third aspect of the present application provides an electrical device, comprising the battery described in the second aspect. The electrical device has all the features and advantages of the battery described above, which will not be described one by one here. DETAILED DESCRIPTION

[0025] The embodiments of the present application are described in detail below, which are intended to be used to explain the present application but should not be construed as limiting the present application.

[0026] In a first aspect, the present application provides an electrolyte solution, comprising a solvent, an electrolyte salt and a first additive, wherein the first additive comprises a difluorosilyl phosphate ester represented by Formula 1 and a boric acid silyl ester represented by Formula 2;

[0027]

[0028] wherein R1, R2 and R3 are each independently selected from any one of H, F, C1-C4 alkyl, C1-C4 fluoroalkyl, C2-C4 alkenyl, C2-C4 fluoroalkenyl, C2-C4 alkynyl, C2-C4 fluoroalkynyl, C5-C7 cycloalkyl, phenyl, R'-substituted phenyl and R"-substituted benzyl;

[0029] R ’ , R" are each independently selected from any one of halogen, C1-C4 alkyl, C2-C4 alkenyl, C2-C4 alkynyl, C1-C4 fluoroalkyl, C2-C4 fluoroalkenyl and C2-C4 fluoroalkynyl;

[0030] R4 to R 12 Each is independently selected from any one of C1-C10 alkyl, C1-C10 haloalkyl, C2-C10 alkenyl, C2-C10 haloalkenyl, C2-C10 alkynyl, C2-C10 haloalkynyl, halogen and cyano.

[0031] This application uses both difluorosilicon phosphate and boric acid silicon ester dual silicon-based system additives, and through the synergistic effect between the two, the comprehensive performance of the electrolyte and the battery is significantly improved. On the one hand, during the battery charging and discharging process, difluorosilicon phosphate can react to produce silanol compounds and condense to form disiloxane-based fluorophosphate compounds, which have the properties of preferential oxidation and reduction and inhibiting solvent reduction; the silicon-based structure has a high reaction activity to the active oxygen components produced by the decomposition of water in the electrolyte or electrode materials, and can construct a stable interface film, improve the flexibility and smoothness of the interface film, and the fluorophosphate structure combines with lithium salts to produce fluorine-containing lithium phosphates, which participate in the film formation process to provide LiF, Li3PO3, and Li for the interface film. x PO y F z The inorganic components of lithium salts such as PO and P=F can enhance the thermal stability and lithium ion conductivity of the interface film; P=O bonds, PO bonds, and P=F bonds can complex transition metals, reduce the amount of transition metals dissolved in the electrolyte, inhibit the catalysis of transition metal ions on the electrolyte, and prevent the reduction and deposition of transition metal ions on the surface of the negative electrode. On the other hand, the electron-deficient boron (B) atom in boric acid silanol can adsorb HF as a Lewis acid and stabilize PF6 -, reducing the damage of HF to the electrode materials and the decomposition of the electrolyte, not only alleviates the corrosion of HF to the electrode materials, but also allows the difluorosilyl phosphate, which is sensitive to HF, to exist stably, and will not react with HF to cause the interface film to be damaged and produce fluorosilane gas. It can also alleviate the electrolyte oxidation sediments that hinder the migration of lithium ions, resulting in a surge in interface impedance and battery capacity attenuation; in addition, the electron-deficient B atoms can complex the transition metal ions dissolved during the charge and discharge process, reducing the catalytic decomposition of the transition metal ions to the electrolyte; at the same time, BO is a low-impedance component, which participates in the construction of the interface film, reduces the interface impedance, makes it easier for active ions to embed and detach, and thus facilitates the transport of lithium ions. The silane component in the borate ester is highly active and can react with HF, further reducing the damage of HF to the electrode materials. In addition, the Si-O component has excellent thermal stability, which is beneficial as a skeleton to improve the heat resistance of the interface film. The electrolyte of the present application uses both difluorosilicon phosphate and silicon borate as additives, which can give full play to the advantages of both. At the same time, the two work together to make up for their respective shortcomings, thereby significantly improving the room temperature cycle, high temperature cycle, high temperature storage and low temperature discharge performance of the battery using the electrolyte.

[0032] It should be noted that the term "C1-C4 alkyl" used in this application refers to a saturated straight-chain or branched monovalent hydrocarbon group containing 1-4 carbon atoms. Examples of C1-C4 alkyl include but are not limited to methyl (-CH3), ethyl (-CH2CH3), n-propyl (-CH2CH2CH3), isopropyl (-CH(CH3)2), n-butyl (-CH2CH2CH2CH3), isobutyl (-CH2CH(CH3)2), sec-butyl (-CH(CH3)CH2CH3), tert-butyl (-C(CH3)3), and the like.

[0033] The term "C1-C4 fluoroalkyl group" means that at least one hydrogen atom in a C1-C4 alkyl group is substituted with a fluorine atom.

[0034] The term "C2-C4 alkenyl" means a straight or branched monovalent hydrocarbon group containing 2-4 carbon atoms, wherein there is at least one unsaturated site, i.e., there is a carbon-carbon sp2 double bond. Examples of C2-C4 alkenyl include, but are not limited to, vinyl (-CH=CH2), allyl (-CH2CH=CH2), 1-propenyl (-CH=CH-CH3), and the like.

[0035] The term "C2-C4 fluoroalkenyl group" means that at least one hydrogen atom in a C2-C4 alkenyl group is substituted with a fluorine atom.

[0036] The term "C2-C4 alkynyl" means a straight or branched monovalent hydrocarbon group containing 2-4 carbon atoms, wherein there is at least one unsaturated site, i.e., there is a carbon-carbon sp triple bond. Examples of C2-C4 alkynyl groups include, but are not limited to, ethynyl (-C≡CH), propargyl (-CH2C≡CH), 1-propynyl (-C≡C-CH3), and the like.

[0037] The term "C2-C4 fluoroalkynyl" means that at least one hydrogen atom in a C2-C4 alkynyl group is substituted with a fluorine atom.

[0038] The term “R ’ Substituted phenyl means that one or more of the five hydrogen atoms on the phenyl group is replaced by R ’ Substitution, the substituted positions include ortho, meta, para, etc.; "R" substituted benzyl" means that one or more of the four hydrogen atoms on the benzene ring in the benzyl group is replaced by R", and the substituted positions include ortho, meta, para, etc.

[0039] The description method "R1, R2, R3 are each independent..." in this article means that R1, R2, R3 are independent of each other and do not affect each other. They can be the same or different. Other similar descriptions have the same meaning.

[0040] In some embodiments, the difluorosilyl phosphate represented by Formula 1 includes at least one of the following compounds:

[0041]

[0042] By using the above-mentioned difluorosilyl phosphate, the thermal stability of the interface film, the lithium ion conductivity, the dissolution amount of the positive electrode transition metal in the electrolyte, the inhibition of the catalysis of the transition metal ions on the electrolyte, and the prevention of the reduction and deposition of the transition metal ions on the negative electrode surface can be further improved.

[0043] In some embodiments, R4 to R 12 Each is independently selected from any one of C1-C4 alkyl, C2-C4 alkenyl, C2-C4 alkynyl, halogen and cyano.

[0044] In some embodiments, the boric acid silyl ester represented by Formula 2 comprises at least one of the following compounds:

[0045]

[0046] By using the above-mentioned boric acid silicon ester, the damage of HF and transition metal ions to electrode materials and the decomposition of electrolyte can be reduced, the interface impedance can be reduced, the active ion transmission can be promoted, and the effect of stabilizing difluorosilicic acid ester can be further improved.

[0047] In some embodiments, based on the total mass of the electrolyte, the amount of the difluorosilicone phosphate shown in Formula 1 is 0.05% to 5%; in other embodiments, the amount of the difluorosilicone phosphate is 0.5% to 2.5%; specifically, it can be 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.2%, 1.5%, 1.8%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, etc. Within the above-mentioned addition amount range, the difluorosilicone phosphate can effectively play the role of constructing a stable interface film, improving the flexibility and flatness of the interface film, and improving the thermal stability and lithium ion conductivity of the interface film, while basically not having a negative impact on the electrolyte.

[0048] In some embodiments, based on the total mass of the electrolyte, the amount of the boric acid silicic acid ester shown in Formula 2 is 0.1% to 1%; in other embodiments, the amount of the boric acid silicic acid ester is 0.3% to 0.7%; specifically, it can be 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, etc. Within the above-mentioned addition amount range, the boric acid silicic acid ester can effectively reduce the damage of HF and transition metal ions to the electrode material and the decomposition of the electrolyte, reduce the impedance of the interface film, and promote the insertion and extraction of lithium ions, while basically having no negative impact on the electrolyte.

[0049] In some embodiments, the electrolyte salt includes at least one of lithium hexafluorophosphate, lithium difluorophosphate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium perchlorate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(oxalatoborate) and lithium difluorooxalatoborate. Further, the electrolyte salt may be lithium hexafluorophosphate, which has high ionic conductivity, low resistance and good chemical stability, so that the lithium ion battery using the electrolyte has the advantages of high energy density and long cycle life.

[0050] It can be understood that the solvent is the main component of the electrolyte and an important carrier for ion transport. The solvent has a high solubility of electrolyte salts, which can make the electrolyte have a high ion conductivity. After the electrolyte salt is dissolved in the solvent, it can release active ions, and the active ions can form a solvation structure with the solvent, which is conducive to the rapid migration of active ions.

[0051] In view of this, in some embodiments, the solvent includes at least one of propylene carbonate, ethyl methyl carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, fluoroethylene carbonate, γ-butyrolactone, cyclopentane, methyl formate, ethyl formate, propyl formate, butyl formate, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, propyl propionate, butyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate, and butyl butyrate. Further, the solvent can be ethylene carbonate, propylene carbonate, diethyl carbonate, and ethyl methyl carbonate, and the mass ratio can be 1.5:1.5:5:2. The solvent in the given range can make the electrolyte have a higher ionic conductivity after dissolving the electrolyte salt, which is beneficial to improve the normal temperature cycle, high temperature cycle, high temperature storage, and low temperature discharge performance of the battery using the electrolyte.

[0052] In some embodiments, based on the total mass of the electrolyte, the mass content of the electrolyte salt is 12% to 17%; in other embodiments, the mass content of the electrolyte salt is 12% to 15%; specifically, it can be 12%, 13%, 14%, 15%, 16%, 17%, etc. As a specific example, the mass content of the electrolyte salt is 12.5%. Within the above mass content range, the electrolyte has better conductivity and electrochemical stability.

[0053] In some embodiments, based on the total mass of the electrolyte, the mass percentage of the solvent is 10% to 90%, for example, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80% or 90%, etc. Within the above mass percentage range, the solvent can better dissolve the electrolyte salt and improve the electrochemical stability.

[0054] The second aspect of the present application proposes a battery, including the aforementioned electrolyte. It should be noted that the characteristics and effects described for the electrolyte in the first aspect of the present application are also applicable to the battery in the second aspect of the present application, and will not be repeated here. In general, the battery has good normal temperature cycle, high temperature cycle, high temperature storage and low temperature discharge performance, and has good comprehensive performance.

[0055] It can be understood that there is no special restriction on the specific type of the battery, which can be a primary battery, a secondary battery (including but not limited to lithium-ion batteries, sodium-ion batteries, etc.); the shape of the battery can be a cylindrical battery, a square battery, and the outer packaging classification can be a hard shell battery, a soft pack battery, etc.

[0056] Typically, a battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, wherein the positive electrode sheet, the negative electrode sheet and the separator can be made into an electrode assembly by winding or lamination process, and the electrode assembly and the electrolyte can be contained in an outer package. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, which mainly plays the role of preventing the positive and negative electrodes from short-circuiting, and at the same time allows ions to pass through.

[0057] In some embodiments, the positive electrode sheet may include a positive current collector and a positive active material layer disposed on the surface of the positive current collector, the positive active material layer including a positive active material, a conductive agent and a binder, and the positive current collector may include a metal foil, for example, the metal foil may be an aluminum foil. The positive electrode active material may include lithium nickel cobalt manganese oxide (including but not limited to NCM811, NCM613, NCM523, etc.), lithium cobalt oxide, lithium iron phosphate, lithium manganese oxide, lithium nickel manganese oxide, lithium-rich manganese-based materials or positive electrode active materials commonly used in the art. The conductive agent may include acetylene black, single-walled carbon nanotubes and conventional materials in the art. The binder may be polyvinylidene fluoride (PVDF) and conventional materials in the art.

[0058] In some embodiments, the negative electrode sheet may include a negative electrode current collector and a negative electrode active material layer disposed on the surface of the negative electrode current collector, and the negative electrode active material layer may include a negative electrode active material, a thickener, a conductive agent, and a binder, wherein the negative electrode current collector may be a metal foil, for example, the metal foil may be a copper foil. The negative electrode active material may include artificial graphite, natural graphite, a silicon-containing carbon-based composite material, a lithium-containing metal composite material, a lithium metal material, and a common negative electrode active material in the art. The thickener may be a thickener sodium carboxymethyl cellulose (CMC-Na) and a conventional material in the art. The conductive agent may be acetylene black and a conventional material in the art. The binder may be styrene-butadiene rubber and a conventional material in the art.

[0059] In some embodiments, the separator may be a separator known in the art that can be used in batteries and is stable to the electrolyte used, such as a polyethylene separator.

[0060] The third aspect of the present application provides an electrical device, including the aforementioned battery. It should be noted that the features and effects described for the battery in the second aspect of the present application are also applicable to the electrical device, and will not be described in detail here.

[0061] According to an embodiment of the present application, the battery can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0062] It can be understood that, in addition to the battery mentioned above, the electrical device may have the necessary structures and components of a conventional electrical device. Taking a car as an example, it may also include a body, windows, chassis, engine, seat interior, tires, etc.

[0063] The embodiments of the present application are described in detail below.

[0064] The difluorosilyl phosphate ester represented by Formula 1 and the boric acid ester represented by Formula 2 used in the following examples can be purchased directly or prepared by yourself. Specifically:

[0065] Compound 1a (CAS No.: 2708941-25-5), compound 1b (CAS No.: 4419-25-9), compound 1c (CAS No.: 4414-27-1), compound 1d (CAS No.: 6231-59-0), compound 1e (CAS No.: 13683-39-1), compound 1f (CAS No.: 6231-57-8), compound 1g (CAS No.: 4414-26-0), compound 1h (CAS No.: 4480-02-8), compound 1i (CAS No.: 2577172-95- 1), Compound 1j (CAS No.: 13683-40-4), Compound 1k (CAS No.: 2577172-93-9), Compound 1l (CAS No.: 2708941-27-7), Compound 1m (CAS No.: 2287283-36-5), Compound 1s (CAS No.: 1386-54-9), Compound 1t (CAS No.: 2708941-26-6), Compound 1u (CAS No.: 6231-58-9), and Compound 1v (CAS No.: 2577172-94-0) can be purchased directly.

[0066] Compounds 1n to 1r can be prepared by referring to the preparation method of Example 14 in patent CN114728992A. Specifically, the following raw materials are used to replace the chlorodimethylphenylsilane in the reference document:

[0067] Raw material: trivinyl chlorosilane (CAS No.: 1871-21-2);

[0068] The raw material is dimethyl butyl chlorosilane (CAS No.: 2069196-19-4);

[0069] The raw material is dimethyl (trifluoropropylene) chlorosilane (CAS No.: 89705-02-2);

[0070] The raw material is tris(pentafluoroethyl)chlorosilane (CAS No.: 1620665-21-5);

[0071] The raw material is dimethyl (p-methylbenzyl) chlorosilane (CAS No.: 1833-28-9);

[0072] Compound 2a (CAS No.: 4325-85-3), compound 2b (CAS No.: 383189-04-6), compound 2c (CAS No.: 2271484-33-2), compound 2d (CAS No.: 2241292-69-1), compound 2e (CAS No.: 2241292-71-5), compound 2f (CAS No.: 2241292-62-4), compound 2g (CAS No.: 691-68-9), compound 2h (CAS No.: 17940-85-1), and compound 2i (CAS No.: 3004856-81-6) can be purchased directly.

[0073] The electrolytes and lithium ion batteries of the examples and comparative examples of the present application were prepared according to the following method:

[0074] 1. Preparation of Electrolyte

[0075] In a glove box filled with argon (water content <10ppm, oxygen content <1ppm), ethylene carbonate EC, propylene carbonate PC, diethyl carbonate DEC, and ethyl methyl carbonate EMC were mixed uniformly at a mass ratio of 1.5:1.5:5:2, and then additives and LiPF6 were added thereto. Among them, based on the total mass of the electrolyte, the mass percentage of LiPF6 is 12.5%, and the types and contents of additives are listed in Table 1.

[0076] 2. Preparation of positive electrode

[0077] 1) Mix the positive electrode active material lithium nickel cobalt manganese oxide (NCM811), the binder polyvinylidene fluoride (PVDF), and the conductive agent acetylene black in a mass ratio of 96.8:1.2:2, add N-methylpyrrolidone (NMP) as a solvent, and prepare a slurry with a solid content of 68wt%, and vacuum stir to obtain a positive electrode slurry. The positive electrode slurry is evenly coated on both surfaces of the positive electrode current collector aluminum foil with a thickness of 16μm, and baked in an oven with different temperature gradients (90℃, 100℃, and 85℃, respectively) at a speed of 2200mm / min, and then dried at 120℃ to obtain a positive electrode sheet with a double-sided positive electrode material layer. After cutting and welding the pole ears, a positive electrode sheet with a specification of 558mm×55mm is obtained for standby use. Among them, the compaction density of the positive electrode material layer is 3.4g / cm 3 The thickness of the single-sided positive electrode material layer is 59μm.

[0078] 2) The positive electrode active material lithium nickel cobalt manganese oxide (613), the binder polyvinylidene fluoride (PVDF), the conductive agent acetylene black, and the single-walled carbon nanotubes are mixed in a mass ratio of 95:1.5:3:0.5, and N-methylpyrrolidone (NMP) is added as a solvent to prepare a slurry with a solid content of 68wt%, and the positive electrode slurry is obtained after vacuum stirring. The positive electrode slurry is evenly coated on both surfaces of the positive electrode current collector aluminum foil with a thickness of 16μm, and baked in an oven with different temperature gradients (90℃, 100℃, and 85℃, respectively) at a speed of 2200mm / min, and then dried at 120℃ to obtain a positive electrode sheet with a double-sided positive electrode material layer. After cutting and welding the pole ears, a positive electrode sheet with a specification of 558mm×55mm is obtained for standby use. Among them, the compaction density of the positive electrode material layer is 3.4g / cm 3 The thickness of the single-sided positive electrode material layer is 44μm.

[0079] 3) Mix the positive electrode active material lithium cobalt oxide, the binder polyvinylidene fluoride (PVDF), and the conductive agent acetylene black in a mass ratio of 97.3:1.2:1.5, add N-methylpyrrolidone (NMP) as a solvent, and prepare a slurry with a solid content of 68wt%, and vacuum stir to obtain a positive electrode slurry. The positive electrode slurry is evenly coated on both surfaces of the positive electrode current collector aluminum foil with a thickness of 16μm, and baked in an oven with different temperature gradients (90℃, 100℃, and 85℃, respectively) at a speed of 2200mm / min, and then dried at 120℃ to obtain a positive electrode sheet with a double-sided positive electrode material layer. After cutting and welding the pole ears, a positive electrode with a specification of 558mm×55mm is obtained for standby use. Among them, the compaction density of the positive electrode material layer is 4.15g / cm 3 The thickness of the single-sided positive electrode material layer is 36μm.

[0080] 4) The positive electrode active material lithium iron phosphate, the binder polyvinylidene fluoride (PVDF), and the conductive agent acetylene black are mixed in a mass ratio of 96:2:2, and N-methylpyrrolidone (NMP) is added as a solvent to prepare a slurry with a solid content of 68wt%, and the positive electrode slurry is obtained after vacuum stirring. The positive electrode slurry is evenly coated on both surfaces of the positive electrode current collector aluminum foil with a thickness of 16μm, and baked in an oven with different temperature gradients (90℃, 100℃, and 85℃, respectively) at a speed of 2200mm / min, and then dried at 120℃ to obtain a positive electrode sheet with a double-sided positive electrode material layer. After cutting and welding the pole ears, a positive electrode sheet with a specification of 558mm×55mm is obtained for standby use. Among them, the compaction density of the positive electrode material layer is 2.3g / cm 3 The thickness of the single-sided positive electrode material layer is 87μm.

[0081] 3. Preparation of negative electrode

[0082] The negative electrode active material artificial graphite, thickener sodium carboxymethyl cellulose (CMC-Na), binder styrene butadiene rubber, and conductive agent acetylene black are mixed in a mass ratio of 95:1.5:2:1.5, and deionized water is added as a solvent to prepare a slurry with a solid content of 49wt%. After vacuum stirring, the negative electrode slurry is obtained. The negative electrode slurry is evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 9μm, and dried at 85°C to obtain a negative electrode sheet with a negative electrode material layer coated on both sides. After cutting and welding the pole ears, a negative electrode sheet with a specification of 708mm×59mm is obtained for standby use. Among them, the compaction density of the negative electrode material layer is 1.6g / cm 3 The thickness of the single-sided negative electrode material layer is 76μm.

[0083] 4. Preparation of Diaphragm

[0084] A polyethylene diaphragm with a thickness of 8 μm was selected.

[0085] 5. Preparation of Lithium-ion Batteries

[0086] The positive electrode sheet, separator and negative electrode sheet are stacked in sequence and then wound to obtain a bare cell that has not been injected with liquid; the bare cell is placed in an outer packaging foil, and the prepared electrolyte is injected into the dried bare cell. After vacuum packaging, standing, forming, shaping, sorting and other processes, a lithium-ion battery is obtained.

[0087] Test method:

[0088] In all the following performance tests, when the positive electrode material in the lithium-ion battery is NCM811, the charge and discharge voltage range is 2.75V~4.2V; when the positive electrode material in the lithium-ion battery is NCM613, the charge and discharge voltage range is 2.75V~4.2V; when the positive electrode material in the lithium-ion battery is lithium cobalt oxide, the charge and discharge voltage range is 2.75V~4.4V; when the positive electrode material in the lithium-ion battery is lithium iron phosphate, the charge and discharge voltage range is 2.75V~3.9V. The charge and discharge cut-off voltages described in the following specific tests are all described based on the positive electrode material being NCM811.

[0089] (1) Normal temperature cycle performance test

[0090] Place the lithium-ion battery in a 25°C constant temperature test box and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature. Charge it to 4.2V at a constant current of 1.0C, then charge it at a constant voltage of 4.2V until the cut-off current is 0.05C, let it stand for 5 minutes, and discharge it to 2.75V at a constant current of 1.0C, and record it as the discharge capacity C1. Cycle this step for 1500 cycles, record the discharge capacity C2 after 1500 cycles, and calculate the lithium-ion battery cycle capacity retention rate. Normal temperature cycle capacity retention rate = C2 / C1×100%.

[0091] (2) High temperature cycle performance test

[0092] Place the lithium-ion battery in a 45°C constant temperature test box and let it stand for 60 minutes to allow the lithium-ion battery to reach a constant temperature. Charge to 4.2V at a constant current of 1.0C, then charge to a cut-off current of 0.05C at a constant voltage of 4.2V, let it stand for 5 minutes, and discharge to 2.75V at a constant current of 1.0C, and record it as the discharge capacity C3. Cycle this step for 1000 cycles, record the discharge capacity C4 after 1000 cycles, and calculate the lithium-ion battery cycle capacity retention rate. High temperature cycle capacity retention rate = C4 / C3×100%.

[0093] (3) High temperature storage performance test

[0094] Place the lithium-ion battery in a 25℃ constant temperature test box and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature. Charge it to 4.2V at a constant current of 1.0C, then charge it at a constant voltage of 4.2V until the cut-off current is 0.05C, take out the lithium-ion battery and test the thickness, record it as h1. Charge it to 4.2V at a constant current of 1.0C, then charge it at a constant voltage of 4.2V until the cut-off current is 0.05C, let it stand for 5 minutes, and discharge it to 2.75V at a constant current of 1.0C, record it as the discharge capacity C5. Charge at a constant current of 1.0C to 4.2V, then charge at a constant voltage of 4.2V to a cut-off current of 0.05C. Place the fully charged battery in a constant temperature test box at 60℃ for 28 days. Take out the lithium-ion battery for testing and record the thickness as h2. Then discharge at a constant current of 1.0C to 2.75V, and the discharge capacity as C6. 60℃ high temperature storage capacity retention rate = C6 / C5×100%, high temperature storage thickness expansion rate = (h2-h1) / h1×100%.

[0095] (4) Low temperature internal resistance (DCIR)

[0096] Place the lithium-ion battery in a -20℃ constant temperature box and let it stand for 4.5 hours to allow the lithium-ion battery to reach a constant temperature. Charge to 4.2V at 1.0C constant current, let it stand for 30 minutes, then discharge at 1.0C constant current for 30 minutes, let it stand for 1 hour, and then discharge at the current corresponding to the 2C rate (I2C) for 10 seconds. Record the voltage values ​​before and after the 2C rate discharge as V1 and V2, respectively, and calculate the DCIR1 of the lithium-ion battery at 50% state of charge (SOC) (the calculation formula of DCIR1 is: DCIR1=(V1-V2) / I2C).

[0097] (5) Low temperature discharge test

[0098] Place the lithium-ion battery in a 25℃ constant temperature test box and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature. Charge it to 4.2V at a constant current of 1.0C, then charge it at a constant voltage of 4.2V to a cutoff current of 0.05C, let it stand for 5 minutes, and discharge it to 2.75V at a constant current of 0.7C, and record it as the discharge capacity C7. Charge the lithium-ion battery to 4.2V at a constant current of 1.0C, then charge it at a constant voltage of 4.2V to a cutoff current of 0.05C, let it stand for 5 minutes, transfer it to a -20℃ constant temperature box, let it stand for 4.5h, allow the lithium-ion battery to reach a constant temperature, and discharge it to 2.75V at a constant current of 0.7C, and record it as the discharge capacity C8. Calculate the low-temperature discharge capacity retention rate of the lithium-ion battery = C8 / C7×100%.

[0099] Table 1

[0100]

[0101]

[0102] Results and conclusion: According to the test results in Table 1 above, the use of difluorosilicone phosphate and boric acid silicon ester dual silicon-based system additives can significantly improve the overall performance of the battery through the synergistic effect between the two.

[0103] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0104] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. An electrolyte, characterized in that: The method comprises a solvent, an electrolyte salt and a first additive, wherein the first additive comprises a difluorosilyl phosphate ester represented by Formula 1 and a boric acid silyl ester represented by Formula 2; wherein R1, R2 and R3 are independently selected from any one of H, F, C1-C4 alkyl, C1-C4 fluoroalkyl, C2-C4 alkenyl, C2-C4 fluoroalkenyl, C2-C4 alkynyl, C5-C7 cycloalkyl, phenyl, R'-substituted phenyl and R"-substituted benzyl; R ’ , R" are each independently selected from any one of halogen, C1-C4 alkyl, C2-C4 alkenyl, C2-C4 alkynyl, C1-C4 fluoroalkyl, C2-C4 fluoroalkenyl and C2-C4 fluoroalkynyl; R4 to R 12 Each is independently selected from any one of C1-C10 alkyl, C1-C10 haloalkyl, C2-C10 alkenyl, C2-C10 haloalkenyl, C2-C10 alkynyl, C2-C10 haloalkynyl, halogen and cyano.

2. The electrolyte according to claim 1, characterized in that The difluorosilyl phosphate represented by Formula 1 includes at least one of the following compounds:

3. The electrolyte according to claim 1, characterized in that R4 to R 12 Each is independently selected from any one of C1-C4 alkyl, C2-C4 alkenyl, C2-C4 alkynyl, halogen and cyano.

4. The electrolyte according to claim 1, characterized in that The boric acid silicon ester shown in Formula 2 includes at least one of the following compounds:

5. The electrolyte according to claim 1, characterized in that Based on the total mass of the electrolyte, the addition amount of the difluorosilyl phosphate represented by Formula 1 is 0.05% to 5%, preferably 0.5% to 2.5%.

6. The electrolyte according to claim 1, characterized in that Based on the total mass of the electrolyte, the addition amount of the boric acid silicon ester represented by Formula 2 is 0.1% to 1%, preferably 0.3% to 0.7%.

7. The electrolyte according to claim 1, characterized in that Satisfy at least one of the following conditions: The electrolyte salt includes at least one of lithium hexafluorophosphate, lithium difluorophosphate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium perchlorate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(oxalatoborate) and lithium difluorooxalatoborate; The solvent includes at least one of propylene carbonate, ethyl methyl carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, fluoroethylene carbonate, γ-butyrolactone, cyclopentane, methyl formate, ethyl formate, propyl formate, butyl formate, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, propyl propionate, butyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate, and butyl butyrate.

8. The electrolyte according to claim 7, characterized in that Based on the total mass of the electrolyte, at least one of the following conditions is met: The mass percentage of the electrolyte salt is 12% to 17%, preferably 12% to 15%; The mass percentage of the solvent is 10% to 90%.

9. A battery, characterized in that: The electrolyte, the positive electrode sheet, the negative electrode sheet and the separator according to any one of claims 1 to 8; The positive electrode sheet may include a positive electrode current collector and a positive electrode active material layer disposed on the surface of the positive electrode current collector, wherein the positive electrode active material layer includes a positive electrode active material, a conductive agent and a binder; The positive electrode active material includes lithium nickel cobalt manganese oxide, lithium cobalt oxide, lithium iron phosphate, lithium manganese oxide, lithium nickel manganese oxide, and lithium-rich manganese-based materials.

10. An electrical device, characterized in that: A battery comprising the battery of claim 9.

Citation Information

Patent Citations

  • Electrolyte additive for lithium secondary battery, electrolyte for lithium secondary battery comprising same, and lithium secondary battery

    CN114402468A

  • Electrolyte and lithium ion battery

    CN116072965A

  • Electrolyte and battery comprising same

    CN118630319A

  • Additive for non-aqueous secondary battery, non-aqueous electrolyte for non-aqueous secondary battery, electrode for non-aqueous secondary battery and non-aqueous secondary battery

    JP2023035933A

Cited By

  • Lithium ion battery

    CN120767413A